2018
DOI: 10.1186/s12864-018-4570-8
|View full text |Cite
|
Sign up to set email alerts
|

Loss of stomach, loss of appetite? Sequencing of the ballan wrasse (Labrus bergylta) genome and intestinal transcriptomic profiling illuminate the evolution of loss of stomach function in fish

Abstract: BackgroundThe ballan wrasse (Labrus bergylta) belongs to a large teleost family containing more than 600 species showing several unique evolutionary traits such as lack of stomach and hermaphroditism. Agastric fish are found throughout the teleost phylogeny, in quite diverse and unrelated lineages, indicating stomach loss has occurred independently multiple times in the course of evolution. By assembling the ballan wrasse genome and transcriptome we aimed to determine the genetic basis for its digestive system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 84 publications
2
55
0
Order By: Relevance
“…Nevertheless, the expression of pepsin is not present in stomachless species such as ballan wrasse L. bergylta (Hansen et al, ) and is negligible in Atherinops affinis (Logothetis et al, ), due to their lack of a functional stomach. Some studies have shown that stomachless fish such as ballan wrasse (Lie et al, ), zebrafish ( Danio rerio ) and medaka ( Oryzias latipes ) have lost the pepsinogen gene, and this loss is correlated with the lack of a stomach function (acid secretion and pepsin activity) (Castro et al, ). It has been suggested that the source of food and changes in the diet to which these organisms were subjected, acted as a driving force for the loss of the stomach (Castro et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the expression of pepsin is not present in stomachless species such as ballan wrasse L. bergylta (Hansen et al, ) and is negligible in Atherinops affinis (Logothetis et al, ), due to their lack of a functional stomach. Some studies have shown that stomachless fish such as ballan wrasse (Lie et al, ), zebrafish ( Danio rerio ) and medaka ( Oryzias latipes ) have lost the pepsinogen gene, and this loss is correlated with the lack of a stomach function (acid secretion and pepsin activity) (Castro et al, ). It has been suggested that the source of food and changes in the diet to which these organisms were subjected, acted as a driving force for the loss of the stomach (Castro et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The dominant expression of Aqp10a and Aqp11 in Segment 1 may be associated with the major digestion and absorption of macronutrients of this section. In some fish species, including the wrasses, triglycerides (TG) are completely hydrolyzed during digestion to free fatty acids and a free glycerol molecule in the intestinal lumen (Lie et al, 2018;Saele et al, 2018). We hypothesize that Aqp10a, which is permeable to glycerol (Madsen et al, 2015), may be involved in glycerol absorption to the enterocytes.…”
Section: Gut Evacuation In the Agastric Fish Ballan Wrassementioning
confidence: 99%
“…Furthermore while also lacking pyloric caeca, agastric fish may have a relatively long intestine measuring several times the animal body length (e.g., bighead carp Aristichthys nobilis) (Opuszynski and Shireman, 1991), which increases the overall surface area of the intestine. However, it remains unknown how efficiently nutrients are digested and absorbed in agastric fish with short digestive tracts such as the ballan wrasse (Figure 1) (Deady and Fives, 1995;Figueiredo et al, 2005;Skiftesvik et al, 2014;Lie et al, 2018;Artüz, 2019). It is also unknown if the wider anterior segment of ballan wrasse functions as a food storage area and thus if the intestinal bulb should be considered a pseudogaster.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, there have been significant investments to domesticate Atlantic cod for aquaculture purposes. Various factors have prevented this industry to be profitable, for instance through difficulties in immunization of juvenile cod (Samuelsen et al, 2006;Froese and Pauly, 2012), but also through to an inefficient digestion of formulated food of larvae in the prestomach stage (Hamre, 2006;Lie et al, 2018). Providing baseline data of the natural composition of intestinal microbiome in Atlantic cod may help efforts to improve the profitability of this industry.…”
Section: Introductionmentioning
confidence: 99%